Design And Evaluation Of A Modified Csma/Cd Mac Protocol On Single-Channel Optical Local Area Network - Khairi, Kharina (2003)
The project carried out was a study of a single-channel optical Local Area Network (LAN) based on an improved CSMA/CD protocol that was adapted from the conventional one. The algorithm of the new version of CSMA/CD was developed, and the LAN was comprehensively studied from a performance perspective within two different scenarios, namely, the Fast Ethernet and the Gigabit Ethernet. The algorithm was developed in Visual Basic 6.0v programming language. This algorithm paved the way for the generation of performance parameters through simulation of the new LAN. The parameters were then studied and compared against corresponding parameters of conventional LAN that are well reported in the literature. The coding of the new algorithm also incorporated a new type of signal known as 'special jamming signal' that served to stop all nodes from attempting to transmit except the one whose number of transmission attempts matched the maximum value specified. This resulted in a condition whereby there was no packet loss at all. The algorithm also focused on providing adequate delay, throughput and efficiency that were needed to support the existing LAN. The results of this study showed that at least two significant contributions; the average delay and the percentage of collisions which were both shown to improve significantly. Additionally, as far as operating environments were concerned, the throughput (measured on a percentage scale) of Fast Ethernet performed better than that of its Gigabit competitor. The difference in their throughput was attributed to the carrier extension mechanism that was employed by the former. Efficiency, on the other hand, did not show any difference in both transmission rates. The summary of the overall performance of our network showed improvement for all parameters under study: delay, throughput, efficiency and percentage of collisions by using the improved CSMA/CD protocol.